VLSI Design and Comparison of DA and LMS Based Reconfigurable FIR Filter - P. Hemanthkumar; Y. Sai Kiran; V. Nava Teja (Institute of Advanced Engineering and Science, 2016)
Here, we exhibit the design optimization of one- and two-dimensional fully-pipelined computing structures for area-delay-power-efficient implementation of finite impulse response (FIR) filter by systolic decomposition of distributed arithmetic (DA)-based inner-product computation. This plan is found to offer a flexible choice of the address length of the look-up-tables (LUT) for DA-based computation to determine suitable area-time trade-off. It is seen that by using smaller address-lengths for DA-based computing units, it is possible to decrease the memory-size but on the other side that leads to increase of adder complexity and the latency. For efficient DA-based realization of FIR filters of different orders, the flexible linear systolic design is implemented on a Xilinx Virtex-E XCV2000E FPGA using a hybrid combination of Handel-C and parameterizable VHDL cores. Various key performance metrics such as number of slices, maximum usable frequency, dynamic power consumption, energy density and energy throughput are estimated for different filter orders and address-lengths. Obtained results on analysis shows that performance metrics of the proposed implementation is broadly in line with theoretical expectations. We have seen that the choice of address-length M=4 gives the best of area-delay power-efficient realizations of the FIR filter for different filter orders. Moreover, the proposed FPGA implementation is found to involve significantly less area-delay complexity compared with the existing DA-based implementations of FIR filter.